Teachers’ Standards in Ghana’s Initial Teacher Education Programme: Some Implementation Issues and Challenges - Eric Daniel Ananga (Journal of Educational Issues, 2024)
Ensuring high standards in the preparation of teachers is critical for the effective professional practice of the Ghanaian teacher. This study examines the National Teachers Standards (NTS) for teachers in Ghana with particular focus on the initial teacher education (ITE) programme, and how tutors and student teachers (mentees) apply the NTS. Adopting a mixed methods approach to the collection of data from participants (368 tutors, 3,600 students of whom 408 are mentees), the findings of this study show that not all of the tutors apply the NTS in their practice as expected. The study also found that few of the student teachers (mentees) demonstrate application of the NTS. In terms of policy, there is a need to deepen further training for tutors if they are all expected to implement the NTS as intended.